2013
DOI: 10.3389/fphar.2013.00098
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant activity: contribution of brain microdialysis in knock-out mice to the understanding of BDNF/5-HT transporter/5-HT autoreceptor interactions

Abstract: Why antidepressants vary in terms of efficacy is currently unclear. Despite the leadership of selective serotonin reuptake inhibitors (SSRIs) in the treatment of depression, the precise neurobiological mechanisms involved in their therapeutic action are poorly understood. A better knowledge of molecular interactions between monoaminergic system, pre- and post-synaptic partners, brain neuronal circuits and regions involved may help to overcome limitations of current treatments and identify new therapeutic targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…Of particular importance, it is not clear what is the biological mechanism behind the variability of efficacy of antidepressants between different individuals. It is presumed that their therapeutic effects are achieved through slow onset auto-receptor down-regulation, and subsequent adaptation of downstream neural signaling pathways, including promotion of neural plasticity 1518 . Besides this, although the antidepressants are considered to be efficient, still the relative risk reduction of relapse by the continuous treatments was estimated to be 50–60% 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Of particular importance, it is not clear what is the biological mechanism behind the variability of efficacy of antidepressants between different individuals. It is presumed that their therapeutic effects are achieved through slow onset auto-receptor down-regulation, and subsequent adaptation of downstream neural signaling pathways, including promotion of neural plasticity 1518 . Besides this, although the antidepressants are considered to be efficient, still the relative risk reduction of relapse by the continuous treatments was estimated to be 50–60% 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that microorganisms in the gut can affect the metabolism of tryptophan, which is a precursor of 5-HT. Microorganisms deplete tryptophan through the canine uric acid pathway, thereby decreasing the amount of 5-HT and causing depression symptoms [17]. Compared with that of the CUMS model group without treatment, 5-HT expression in the hippocampus of TIV-M, TIV-H, and fluoxetine groups significantly increased (p < 0.01).…”
Section: Resultsmentioning
confidence: 95%
“…Regulation of presynaptic and postsynaptic serotonin ( Gardier et al, 1992 , 2013 ; Erfurth et al, 1994 ; Spies et al, 2015 ; James et al, 2017 ; Kraus et al, 2017 ) is a central strategy in psychopharmacology. Selective serotonin reuptake inhibitors (SSRIs) are a leading option in the treatment of major depression ( Schatzberg, 1996 ; Dold et al, 2016 ; Novak and Erfurth, 2017 ), anxiety disorders ( Kasper, 2006 ), and OCRDs including OCD ( Soomro et al, 2008 ).…”
mentioning
confidence: 99%